HIGH-DOSE AMOXICILLIN FOR H. PYLORI GASTRITIS IN CHILDREN: A CASE-SERIES STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the efficacy and safety of a high-dose Amoxicillin regimen in the treatment of gastritis associated with Helicobacter pylori (H. pylori) infection in children in Vietnam.Subjects and methods: A cross-sectional descriptive study was conducted on 50 pediatric patients under 16 years of age (mean age 7.46 ± 3.01 years) diagnosed with first-time H. pylori-associated gastritis and treated at Thanh Hoa Pediatric Hospital. The treatment regimen included high-dose Amoxicillin (75-100 mg/kg/day, divided into two doses for 2 weeks) combined with other antibiotics and a proton pump inhibitor (PPI).Results: After treatment, significant improvements were observed in clinical symptoms: abdominal pain decreased from 100% to 36%, vomiting and nausea from 60% to 8%, belching and acid reflux from 24% to 2%, and bloating and indigestion from 14% to 2%. Minimal adverse events were reported, with abdominal pain in 4% of cases and vomiting or diarrhea in 2%. The eradication rate of H. pylori was 44%.Conclusion: The high-dose Amoxicillin regimen improved clinical symptoms in children with H. pylori-associated gastritis. However, the low eradication rate suggests a high prevalence of Amoxicillin resistance in Vietnam. Further studies with larger sample sizes and a control group are needed to identify more effective treatment strategies tailored to local antibiotic resistance patterns.